(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
In the article, instead of shovels in the inner part of the drum, concave-shaped shovels were installed, and in the middle of the concave-shaped shovels, stakes made of wire (prut) with a height of 150 mm and a diameter of 18 mm were installed. As a result, it is possible to throw the cotton into the useless zone of the inner chamber of the drying drum, and to dry the seeded cotton evenly over the entire surface of the drum. Throwing the cotton in the useless zone and ripping it, in turn, allows to accelerate the release of moisture in the seeded cotton and makes it possible to efficiently use the heat of the hot air supplied to the drum